Ultrasound-Assisted Chin Liposuction under Local Anesthesia: An Effective Tool for Facial Slimming in Indian Population - Shruti Marwah; Arjun Handa (Indian Journal of Plastic Surgery)
An aesthetically pleasing neck is an important component of a youthful appearance of the face. It is frequently targeted by many surgical and nonsurgical methods to achieve the best results. Today, patients are looking for a minimally invasive option that gives permanent results and has a quick recovery. Therefore, ultrasound-assisted liposuction of the chin and jawline has become an important part of the cosmetic surgeon's armamentarium. The objective of this article is to describe the technique, mechanism of action, and most common complications and to establish ultrasound-assisted face liposuction under local anesthesia as an effective method to achieve facial slimming especially in the Indian population.